2013
DOI: 10.1016/j.bmc.2012.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Effects on polo-like kinase 1 polo-box domain binding affinities of peptides incurred by structural variation at the phosphoamino acid position

Abstract: Protein-protein interactions (PPIs) mediated by the polo-box domain (PBD) of polo-like kinase 1 (Plk1) serve important roles in cell proliferation. Critical elements in the high affinity recognition of peptides and proteins by PBD are derived from pThr/pSer-residues in the binding ligands. However, there has been little examination of pThr/pSer mimetics within a PBD context. Our current paper compares the abilities of a variety of amino acid residues and derivatives to serve as pThr/pSer replacements by explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 71 publications
(56 reference statements)
0
13
0
Order By: Relevance
“…We have shown that pThr provides a 5-fold enhancement in binding affinity versus the pSer-containing peptide ( 6 ). 12,13 Presumably, this affinity enhancement is due to the 3 R -methyl group restricting the side chain rotation (or χ 1 angle) in a favorable binding orientation. 14 More importantly, we have also shown that the pThr residue in 5 can be replaced with Pmab to produce a phosphatase-stable peptidomimetic (peptide 7 ) having complete retention of inhibitory potency.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that pThr provides a 5-fold enhancement in binding affinity versus the pSer-containing peptide ( 6 ). 12,13 Presumably, this affinity enhancement is due to the 3 R -methyl group restricting the side chain rotation (or χ 1 angle) in a favorable binding orientation. 14 More importantly, we have also shown that the pThr residue in 5 can be replaced with Pmab to produce a phosphatase-stable peptidomimetic (peptide 7 ) having complete retention of inhibitory potency.…”
mentioning
confidence: 99%
“…14 More importantly, we have also shown that the pThr residue in 5 can be replaced with Pmab to produce a phosphatase-stable peptidomimetic (peptide 7 ) having complete retention of inhibitory potency. 13,15,16 Unfortunately, the use of Pmab in further ligand development is significantly hindered by relatively inefficient synthetic access to orthogonally-protected Pmab constructs that are compatible with solid-phase peptide synthesis (SPPS). In this work, we have developed a more direct synthetic route to SPPS-compatible Pmab analogs.…”
mentioning
confidence: 99%
“…Unfortunately, the reagent N -Fmoc-His-[ N(π) -(CH 2 ) 8 Ph]-OH, 13 which is currently used to incorporate H* residues into peptides, requires a lengthy synthesis. 8,9,11,14-18 This has made difficult a direct examination of different functionality at the N(π) -position. In our current work we explore binding motifs originating from the His N(π) -position using a “tethered fragment” methodology that employs oxime ligation.…”
mentioning
confidence: 99%
“…These values are approximately 10-fold higher than our previously reported ELISA IC 50 values for the same peptides. 8,13,14 We attribute this to differences in binding affinities of the immobilized competitor peptides used for these assays. We used oxime-containing peptide 5a-5 as a reference (the second digit indicates the number of methylene units in the tether), since its phenyl group is tethered eight units from the His residue (based on five methylenes and the three members of the oxime linker) similar to the eight methylenes in the tether chain of the parent peptide 2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation